Analisis Kepatuhan Manajemen Usaha yang Bersertifikat Halal Berdasarkan Sistem Jaminan Produk Halal (SJPH): Studi Kasus Getuk Goreng 128 di Sumbang, Banyumas - Widia Eka Restiani; Ayu Rahma Khoerunisa; Afit Rahayu Lestari Ningsih; Mahardika Cipta Raharja; Siti Ma’sumah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This study aims to analyze the level of management compliance of halal-certified businesses through the implementation of the Halal Product Assurance System (SJPH), using a case study of the Getuk Goreng 128 MSME in Sumbang, Banyumas. The background to this research stems from increasing public awareness of the importance of halal products and the challenges faced by MSMEs in maintaining consistent SJPH implementation after obtaining certification. This study used a descriptive qualitative method. The results indicate that Getuk Goreng 128 has a good level of compliance with the SJPH, as reflected in management's commitment to product halalness, the use of halal-certified raw materials, and the implementation of production and hygiene processes in accordance with applicable standards. This compliance is driven by the awareness and responsibility of the business owner, consumer trust, support from the local government, and motivation to develop the business. However, challenges remain, particularly related to limited human resources. Overall, the implementation of the SJPH at Getuk Goreng 128 has a positive impact on increasing consumer trust and strengthening the competitiveness of local halal products.